تعليم اللغة العربية عبر ثقافتها: برامج يابانية فرانكفونية أمريكية في جامعة حلب نموذجا - Chik, Abdul Rahman; Jamous, Rawya (IIUM Press, 2011)
In the struggle to prove the perseverance of ؤivilizations, some nations tend to cancel the identities of others. In this regard, Muslims must have their own position derived from the age long experience of the Islamic civilization in order to strike the same chord between the various nations and peoples of the Islamic belief. This experience is far away from denying the identities of the others but rather it nurtured these differences and enabled the diverse races and religions to contribute to a common cause to develop knowledge, culture and civilization. As of today, it is a challenge to put back this practice at the frontline of own cultures and blend with the otherness as it used to be. Perhaps, through the teaching of Arabic to the non-Arabs is one of the best approaches to expose the Arabic Islamic culture to the others since language itself is a live representative of the culture of its speakers.